PERENCANAAN STRUKTUR KONDOTEL GRAND DARMO SUITE SURABAYA - Lumbantobing, Elfrida Gresih; Nababan, Septesen; Atmanto, Indrastono Dwi; Sukamta, Sukamta (Jurnal Karya Teknik Sipil, 2013)
Structure Condotel Grand Darmo Suite Surabaya planned 13 floors and is located in the region quake 2. The final task is to plan the structure of the building of reinforced concrete using System Frame bearers Special Moment (SRPMK). Building System model frame bearers Special Moment (SRPMK) using the concept of Strong Column and Weak Beam (strong column and weak beam) in accordance with SNI 03-2847-2002 and SNI-1726-2002. Planning the structure of the building using the concept of design capacity. Structure is reviewed by using the analysis of load effects equivalent static and structural analysis calculated with the help of the program SAP2000 v11. Results of the structural design Condotel Grand Darmo Suite Surabaya consisting of concrete frame with reinforcement diameter (D22, D19, D16, D13, and P10), shear wall thickness of 25 cm, the roof using a reinforced concrete slab and foundation using concrete piles precast diameter of 40 cm and 50 cm. Calculations that have been done show that all elements of the building structure is safe in the analysis.